Infant mortality: a Turkish puzzle? - (:unkn) unknown (My University, 1992)
In this paper I examine the problem of high infant and child mortality in Turkey. In view of my research results, I argue for a re-evaluation of the theoretical paradigm that views childhood issues primarily in relation to mothers rather than within the dynamics of a broader cultural context. The present emphasis on mothers as a primary key to the problem reflects an extensive and implicit conceptualization of 'motherhood' that has penetrated scientific discourse and methodology. The research results presented here show that in our Istanbul sample most of the factors related to high child mortality are household and cultural conditions encircling the mother, and that only a few of the factors are direct attributes of the mother herself. These results have significant implications for research and policy on child health.
Keywords: Adult; Female; Humans; Middle Aged; Turkey; Infant; Male; Child; Health Policy; Child, Preschool; Family; Socioeconomic Factors; Smoking; Alcohol Drinking; Mothers; Abortion, Induced; Attitude; Child Welfare; Culture; Infant Mortality; Mortality; Research; Urban Population